THE STUDY OF GRAPHENE BAND GAP USING HATREE FOCK METHOD IN MOLECULAR SCALE - Siti Alaa; Muhammad Fajrin; Eva Nurhaliza; Dian Wijaya Kurniawidi; Susi Rahayu; I Wayan Sudiarta (Universitas Mataram, 2020)
Graphene is known as an advanced material that has good electrical conductivity and heat conductivity. To understand the nature of graphene it is necessary to calculate the energy, band gap and vibrate frequency at the nanoscale. One method that can be used is the ab initio calculation using the Hatree-Fock method. In this research, we performed a computational study of the electronic properties of grapheme within RHF/STO-3G basis set in different cluster molecules. From this study we get band gap for graphene in ab initio level, have a consistant value around zero. Using ab initio method, we can obtain a deeper understanding about the graphene behaviour at the molecular scale.